The Impact of Recitation and Zikr Tastafi on Religious Social Life; Studies in the City Areas of Banda Aceh, Pidie, and North Aceh - Muhammad Arifin (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2023)
As a religious nation, Indonesia places religion as the basis for moral, spiritual, and ethical development. Majelis ta'lim is an Islamic non-formal educational institution that has its position in society because the ta'lim assembly is a forum for fostering and developing religious life to form a pious community to Allah SWT. In Aceh, one of the ta'lim assemblies that have an important role in people's lives is the Majlis Zikir Tastafi (Sufism, Tawhid, and Fiqh). Majlis Tastafi is unique compared to others, with a busy congregation spread throughout Aceh with a good network and organizational structure. This study aims to examine the impact of Tastafi's recitation and remembrance on the socio-religious life of the community and to see the community's interest in attending the recitation. This study uses qualitative methods with an in-depth interview and meticulous observation techniques. The results showed that Tastafi's recitation and remembrance had a good impact on the socio-religious life of the community. In addition, the community's interest in participating in Tastafi's recitation and remembrance was very high because it is driven by the desire to gain religious knowledge and inner strength through zikr.